Cleavage between Replicase Proteins p28 and p65 of Mouse Hepatitis Virus Is Not Required for Virus Replication - Denison, Mark R. (American Society for Microbiology, 2004)
The p28 and p65 proteins of mouse hepatitis virus (MHV) are the most amino-terminal protein domains of the replicase polyprotein. Cleavage between p28 and p65 has been shown to occur in vitro at cleavage site 1 (CS1), (247)Gly↓Val(248), in the polyprotein. Although critical residues for CS1 cleavage have been mapped in vitro, the requirements for cleavage have not been studied in infected cells. To define the determinants of CS1 cleavage and the role of processing at this site during MHV replication, mutations and deletions were engineered in the replicase polyprotein at CS1. Mutations predicted to allow cleavage at CS1 yielded viable virus that grew to wild-type MHV titers and showed normal expression and processing of p28 and p65. Mutant viruses containing predicted noncleaving mutations or a CS1 deletion were also viable but demonstrated delayed growth kinetics, reduced peak titers, decreased RNA synthesis, and small plaques compared to wild-type controls. No p28 or p65 was detected in cells infected with predicted noncleaving CS1 mutants or the CS1 deletion mutant; however, a new protein of 93 kDa was detected. All introduced mutations and the deletion were retained during repeated virus passages in culture, and no phenotypic reversion was observed. The results of this study demonstrate that cleavage between p28 and p65 at CS1 is not required for MHV replication. However, proteolytic separation of p28 from p65 is necessary for optimal RNA synthesis and virus growth, suggesting important roles for these proteins in the formation or function of viral replication complexes.